Impact of electron concentration on the transformation temperature and important physical properties of NiMnSnFe ferromagnetic shape memory alloys - Malkoc, Turkan; Kanca, Muhammed Sait; Isik, Erdem; Kok, Mediha (Springer Heidelberg, 2023)
This study aimed to explore the influence of electron concentration on the NiMnSn alloy, which is a crucial ferromagnetic shape memory alloy (FSMA). The alloy was doped with various amounts of iron element to assess its effect. According to DSC measurement, iron doping has resulted in a general decrease in the transformation temperature value of NiMnSn alloy, as well as a decrease in the transformation enthalpy value. The orthorhombic martensite phase of NiMnSn alloy was replaced by L2(1) austenite crystal structure in X-ray measurements. Martensite, austenite, and precipitate phases were observed in SEM images. Iron doping significantly increased the magnetic saturation value of NiMnSn alloy, according to magnetic measurements, and thermomagnetic measurements revealed similar results.
Keywords: Shape memory; Ferromagnetic; Phase transformation; Alloy; Magnetic properties